Kinetics of malachite leaching in alkaline glycine solutions. Issue 1 (2nd January 2021) - Tanda, B. C.; Oraby, E. A.; Eksteen, J. J.
ABSTRACT: Aqueous alkaline glycine solutions present technical advantages over acidic solutions for leaching oxidised copper minerals hosted in carbonate mineral matrix phases. In this study, the leaching and kinetics of malachite in alkaline glycine solutions have been studied. The influence of process variables such as glycine concentration, temperature, particle size and stirring speed on leaching kinetics was evaluated. The results show that temperature has a significant effect on copper dissolution rates. A temperature increase from 25°C to 50°C resulted in a copper extraction of 32.3–83.6% respectively over 5 min. Increasing glycine concentration and reducing particle size led to an increase in copper extraction rates while no significant influence was observed with stirring speeds above 350 rpm.